Analisis Desain Kegiatan Laboratorium Pertumbuhan dan Perkembangan Tumbuhan: (Design Analysis of Plant Growth and Development Laboratory Activities) - Trisna Dewi; Sri Anggraeni; Bambang Supriatno (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2021)
The Industrial Revolution 4.0 or The Fourth Industrial Revolution (4IR) is a concept of developing education through the use of technological developments. The quality of education must be continuously improved through the transformation of the educational paradigm which emphasizes learning oriented to higher order thinking skills or often referred to as Higher Order Thinking Skills. One way to improve the quality of education is practicum activities using practicum Student Worksheets (LKS). This study aims to provide an overview of the problems of blood structure practicum worksheets in high school. This research is a qualitative descriptive study and the subject of this research is the worksheets of blood structure practicum. The sampling technique used was total sampling, the sample consisted of 6 LKS. The instruments used include relevance analysis instruments, competency analysis and practical analysis as well as knowledge construction analysis. Based on the results of the analysis and trial of the work steps on one of the DKL regarding the material for plant growth and development, several shortcomings were found. These shortcomings are found in the work steps, tools and materials used and the presentation of observational data for most of the DKL. The reconstruction of DKL produces alternatives to DKL for plant growth and development by considering and completing the shortcomings of the analysis results from DKL that have been analyzed. This DKL reconstruction is expected to be able to construct students' knowledge well through practical activities carried out and be able to get 4C skills or 21st century skills needed today. Abstrak. Revolusi Industri 4.0 atau The Fourth Industrial Revolution (4IR) merupakan konsep pengembangan pendidikan melalui pemanfaatan perkembangan teknologi. Mutu pendidikan harus terus ditingkatkan melalui transformasi paradigma pendidikan yang menekankan pada pembelajaran berorientasi keterampilan berpikir tingkat tinggi atau sering disebut dengan Higher Order Thinking Skills. Salah satu cara untuk meningkatkan kualitas pendidikan yaitu dengan kegiatan praktikum menggunakan Lembar Kerja Siswa (LKS) praktikum. Penelitian ini bertujuan untuk memberikan gambaran mengenai permasalahan LKS praktikum struktur darah di SMA. Penelitian ini merupakan penelitian deskriptif kualitatif dan subjek penelitian ini adalah LKS praktikum struktur darah. Teknik sampling yang digunakan yaitu total sampling, sampel terdiri dari 6 LKS. Instrumen yang digunakan meliputi instrumen analisis relevansi, analisis kompetensi dan analisis praktikal serta analisis konstruksi pengetahuan. Berdasarkan hasil analisis dan uji coba Langkah kerja terhadap salah satu DKL. mengenai materi pertumbuhan dan perkembangan tumbuhan ditemukan beberapa kekurangan. Kekurangan tersebut didapatkann pada langkah kerja, alat dan bahan yang digunakan serta penyajian data pengamatan Sebagian besar DKL. Rekontruksi DKL menghasilkan alternatif DKL pertumbuhan dan perkembangan tumbuhan dengan mempertimbangkan dan melengkapi kekurangan hasil analisis dari DKL yang sudah di analisis. Rekontruksi DKL ini diharapkan mampu mengkontruksi pengetahuan peserta didik dengan baik melalui kegiatan praktikum yang dilakukan serta mampu mendapatkan keterampilan 4C atau keterampilan abad 21 yang dibutuhkan saat ini.